Influence of supplemental vitamin D on intensity of benign paroxysmal positional vertigo: A longitudinal clinical study - Mahboobeh Sheikhzadeh; Yones Lotfi; Abdollah Mousavi; Behzad Heidari; Mohsen Monadi; Enayatollah Bakhshi (Babol University of Medical Sciences, 2016)
Background: Benign paroxysmal positional vertigo (BPPV) is linked to vitamin D deficiency. This clinical trial aimed to determine the influence of vitamin D supplementation on intensity of BPPV. Methods: The study population was selected consecutively and the diagnosis of BPPV was made by history and clinical examination and exclusion of other conditions. Intensity of BPVV was assessed based on VAS score (0-10). Serum 25-hydroxyvitamin D (25-OHD) was measured using ELISA method and levels < 20 ng/ml was considered a deficiency. All patients received rehabilitation treatment using Epley's maneuver one time per week for one month. Serum 25-OHD deficient patients were classified as treated and non-treated groups (rehabilitation with or without 50.000 IU cholecalciferol weekly for two months).The results of treatment were compared with vitamin D sufficient group as control. All patients were followed-up for 6 months. Results: After two months of treatment, in both vitamin D treated and non-treated groups the intensity of BPPV decreased significantly as compared with control (P=0.001 for both groups) but at endpoint, the intensity of BPPV aggravated and regressed to the baseline value in vitamin D deficient non-treated group (P=0.001) whereas, in vitamin D treated group, improvement of BPPV remained stable and unchanged over the study period. Conclusion: This study indicates that correction of vitamin D deficiency in BPPV provides additional benefit to rehabilitation therapy (Epley maneuver) regarding duration of improvement. These findings suggest serum 25-OHD measurement in recurrent BPPV.